Leveraging SME finance through value chains in landlocked CAREC countries: Overview - Peter J. Morgan; Akerke Nurgaliyeva; Dossym Kydyrbayev (Asian Development Bank Institute (ADBI), 2019)
This study takes stock of the challenges faced by small and medium-sized enterprises (SMEs) in the CAREC landlocked economies in terms of their access to finance resulting from demand-side, supply-side and institutional constraints. This includes identifying cultural, procedural, institutional and regulatory incentives, disincentives and barriers faced by SMEs to access finance, and the reasons for the lack of such access. It also assesses opportunities of SMEs to link with both domestic and global value chains and the potential impact of this on their access to finance. Finally, it proposes policy recommendations to improve the access of the SMEs to finance and trade finance, especially in the agri-business sector, in light of best global practices including PRC's program to nurture and support SMEs with regards to effective regulatory frameworks, access to finance (banks, capital markets, start-up finance and non-traditional micro-lending or community lending, risk capital), special programs funded by foreign donor institutions, guarantee schemes, improving skills (entrepreneurial training), encouraging networking among SMEs, and use of information and communication technology.
Keywords: F1; G2; G21; G28; H25; O16; O19; Q14; 330; Financial inclusion; SMEs; banks; micro-finance institutions (MFIs); financial literacy; financial education; global value chains (GVCs)